IMPLEMENTASI MEDIA EDUKASI BERUPA POP UP BOOK DALAM MENINGKATKAN KETERAMPILAN MEMBACA SISWA PADA PEMBELAJARAN BAHASA INDONESIA DIKELAS 1 SDNU METRO - Rika Setianingsih; Muhammad Ngali Zainal Makmun; Lutfi Fadillah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading skills are fundamental competencies that play an important role in supporting the success of students' learning process in elementary schools, especially in the early grades. Based on observations in grade I of SDNU Metro, it is known that students' reading skills are still in the low category, as indicated by difficulties in recognizing letters and their sounds, combining letters into words, and understanding simple reading. These problems are influenced by the lack of variety in learning methods and the limited use of interesting learning media that are appropriate to the developmental stage of students. This study aims to analyze the implementation of pop-up book-based educational media and its impact on improving students' reading skills in Indonesian language learning in grade I of SD NU Metro. The study used a quantitative approach with an experimental method. Data collection was carried out through observation, interviews, pre-tests and post-tests, and documentation, while data analysis included normality tests, homogeneity tests, and t-tests. The results of the study are expected to show that the use of pop-up book media can significantly improve students' reading skills, making it worthy of being used as an effective and innovative learning medium in early elementary school.